Determination of Contunuity of Sustainable Green Financial Behavior of Generation Z Islamic Banks (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This research seeks to investigate the post-usage continuation behavior of customers in the green finance sector, utilizing the Extended Social Help (SST) theory as its theoretical framework. The data utilized in this research consists of a questionnaire administered to respondents who are customers of Islamic banks owning to Generation Z. The research outcomes obtained through the application of the Partial Least Squares (PLS) technique indicate that Environmental Consciousness, when mediated by customer satisfaction, does have a negative influence on the continuity of green finance behavior. Similarly, the outcomes align with those of Green Bank Marketing Initiatives (GBMI), which, when mediated by customer satisfaction, also exhibit a negative influence on green finance continuity behavior. Conversely, the Conciliation of customer satisfaction in the object of psychological reactance and its influence on green finance continuity behavior yields a good influence.